Pengembangan Sistem Informasi Untuk Meningkatkan Transparansi Pengelolaan Dana Desa di Kahale Berbasis Web - Nopiana Bili; Ardiyanto Dapadeda; Sihang Gregorius Bali Mema (Yayasan Kawanad, 2026)
Village fund management in Kahale Village faces persistent manual administrative challenges that have eroded public trust, largely due to restricted access to financial information. A web-based information system was developed to address these shortcomings and improve the transparency of village financial governance. The research employed a qualitative descriptive approach for field problem analysis, paired with the Waterfall model for structured software development. Findings indicate that the deployment of monitoring and dashboard features substantially digitized previously manual administrative processes. Report preparation and validation time dropped from three to five days to under twenty-four hours, with data updated in real time. The system also provides centralized digital document storage, which has simplified leadership verification and strengthened internal accountability. Each financial document must pass through a two-stage control mechanism — data entry by the admin and approval by the village head — before it is considered valid and accessible to the public. This digitization effort establishes a reliable foundation for accurate financial data presentation and offers a direct answer to the chronic inefficiencies of conventional record-keeping in supporting public transparency.